2014
DOI: 10.1128/jb.01681-14
|View full text |Cite
|
Sign up to set email alerts
|

Error-Prone Processing of Apurinic/Apyrimidinic (AP) Sites by PolX Underlies a Novel Mechanism That Promotes Adaptive Mutagenesis in Bacillus subtilis

Abstract: cIn growing cells, apurinic/apyrimidinic (AP) sites generated spontaneously or resulting from the enzymatic elimination of oxidized bases must be processed by AP endonucleases before they compromise cell integrity. Here, we investigated how AP sites and the processing of these noncoding lesions by the AP endonucleases Nfo, ExoA, and Nth contribute to the production of mutations (hisC952, metB5, and leuC427) in starved cells of the Bacillus subtilis YB955 strain. Interestingly, cells from this strain that were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
32
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 22 publications
(34 citation statements)
references
References 48 publications
2
32
0
Order By: Relevance
“…These results suggest the existence of alternative repair pathways that compensate for the absence of MutM; in agreement with this notion, the genomes of the three microorganisms discussed above contain the gene for Nth, a DNA glycosylase capable of processing 8-oxo-G and AP sites (40)(41)(42). In the case of B. subtilis, it was recently shown that the genetic inactivation of Nth not only increases this bacterium's spontaneous Rif r mutation frequency but also sensitizes it to the ROS promoter agent H 2 O 2 (33).…”
Section: Resultsmentioning
confidence: 64%
See 2 more Smart Citations
“…These results suggest the existence of alternative repair pathways that compensate for the absence of MutM; in agreement with this notion, the genomes of the three microorganisms discussed above contain the gene for Nth, a DNA glycosylase capable of processing 8-oxo-G and AP sites (40)(41)(42). In the case of B. subtilis, it was recently shown that the genetic inactivation of Nth not only increases this bacterium's spontaneous Rif r mutation frequency but also sensitizes it to the ROS promoter agent H 2 O 2 (33).…”
Section: Resultsmentioning
confidence: 64%
“…Taken together, these results strongly suggest that MutM plays a significant role in preventing the cytotoxic effects of 8-oxo-G and possibly of other related lesions, including the opened ring derivative formamidopyrimidine (FaPy) (29)(30)(31)(32), thus contributing to B. subtilis survival. However, in addition to inducing the formation of oxidized bases, H 2 O 2 and PQ may promote other types of DNA lesions, including 8-OxoG·A mispairs and apurinic/apyrimidinic (AP) sites, as well as single-and/or double-strand DNA breaks (33). Therefore, in addition to MutM, other repair proteins, including MutY, Nth, and the AP-endonucleases Nfo and ExoA, most probably contribute to protecting B. subtilis from the genotoxic effects of H 2 O 2 (33).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To obtain strains harboring a transcriptional aag-lacZ fusion, the integrative vector pMUTIN4 (28) or a chloramphenicol-resistant variant of this plasmid, pMUTIN4cat (29), was utilized. For recombinant plasmid construction, a 360-bp HindIII/BamHI internal fragment of aag (positions ϩ121 to ϩ 480 relative to the aag start codon) was amplified by PCR using chromosomal DNA of B. subtilis 168 and Vent DNA polymerase (New England BioLabs, Ipswich, MA).…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, repair of deaminated cytosine in B. subtilis by the uracil DNA glycosylase Ung and the endonuclease V YwqL occurs in an error-prone manner, promoting adaptive mutagenesis (19). A recent report revealed that the numbers of spontaneously or enzymatically generated apurinic/apyrimidinic (AP) sites increase during the stationary phase in B. subtilis and that such lesions can be processed in an error-prone manner by the low-fidelity (LF) DNA polymerase PolX (20). Other reports have documented the participation of LF DNA polymerases, including YqjH (a member of the Y DNA polymerase family), in generating mutations in nutritionally stressed B. subtilis cells (21).…”
mentioning
confidence: 99%